DISTRIBUTION OF NATURAL RADIONUCLIDES 40K AND 208Tl IN SURFICIAL SEDIMENTS OF SEMARANG WATERS - Dwi P. Sasongko (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Distribution of natural radionuclides in surficial sediments of Semarang waters has been carried out by applying the gamma spectrometry analysis. Using the gamma spectrometry technique was employed to analyze the radiation exposure. Six natural radionuclides (K, TI, Pb, Pb, Ac and Ra) can be identified in sediments, along with two natural radionuclides (K and TI) in water. Distribution factor can be estimated from the ratio of these radionuclides in surficial sediment and the water. Result shows that the distribution factor for radionuclide K is 24.5097 – 33.5206 and for TI is 13.4383 – 42.1509.